A Delphi study to identify key gait patterns and their potential causes in people with multiple sclerosis - Sjoerd T. Timmermans; Marjolein M. van der Krogt; Marc B. Rietberg; Heleen Beckerman; Vincent de Groot (Journal of Rehabilitation Medicine)
Objective: This study aims to identify characteristic gait patterns in people with multiple sclerosis, to describe their key characteristics, and to identify their potential underlying causes.